PERBANDINGAN EFEKTIVITAS MADU TRIGONA DAN MADU SIDR DIKOMBINASIKAN DENGAN MINYAK JINTAN HITAM (Nigella sativa) SEBAGAI HEPATOPROTEKTOR TIKUS WISTAR (Rattus norvegicus) YANG DIINDUKSI PARASETAMOL - AQILAH HANIFA; DES SURYANI (LP2MTBM MAKARIOZ, 2023)
Paracetamol is an antipyretic and analgesic that is often used, but the use of excessive doses can cause hepatotoxicity. Black cumin oil and honey have been shown to have benefits for treating various health problems, especially protecting the liver from hepatotoxicity. Sidr honey is a monofloral honey produced by Apis mellifera bees. Trigona honey is a multi floral honey produced by Trigona sp. To compare the effectiveness of black cumin oil plus trigona honey with black cumin oil plus sidr honey on the liver function of rats induced by paracetamol. Experimental research with posttest only with controlled group design. A total of 4 groups were treated for 28 days. SGOT and SGPT levels were tested. Data analysis used one-way ANOVA post hoc Bonferroni. There was an effect of giving a single dose of paracetamol 2 g/kgBW on liver function of rats characterized by increased levels of SGOT and SGPT in the Positive Control group, there was no significant difference in giving black cumin oil at a dose of 2 ml/kgBW plus sidr honey at a dose of 1 g/kgBW and Black cumin oil at a dose of 2 ml/kgBW plus trigona honey at a dose of 7,4 ml/kgBW for 28 days on the liver of rats that had been induced by paracetamol (p>0.05).The administration of toxic doses of paracetamol caused a decrease in the liver function of rats. The combination of black cumin oil with sidr honey and trigona honey has the same hepatoprotective effectiveness. Paracetamol is an antipyretic and analgesic that is often used, but the use of excessive doses can cause hepatotoxicity. Black cumin oil and honey have been shown to have benefits for treating various health problems, especially protecting the liver from hepatotoxicity. Sidr honey is a monofloral honey produced by Apis mellifera bees. Trigona honey is a multi floral honey produced by Trigona sp. To compare the effectiveness of black cumin oil plus trigona honey with black cumin oil plus sidr honey on the liver function of rats induced by paracetamol. Experimental research with posttest only with controlled group design. A total of 4 groups were treated for 28 days. SGOT and SGPT levels were tested. Data analysis used one-way ANOVA post hoc Bonferroni. There was an effect of giving a single dose of paracetamol 2 g/kgBW on liver function of rats characterized by increased levels of SGOT and SGPT in the Positive Control group, there was no significant difference in giving black cumin oil at a dose of 2 ml/kgBW plus sidr honey at a dose of 1 g/kgBW and Black cumin oil at a dose of 2 ml/kgBW plus trigona honey at a dose of 7,4 ml/kgBW for 28 days on the liver of rats that had been induced by paracetamol (p>0.05).The administration of toxic doses of paracetamol caused a decrease in the liver function of rats. The combination of black cumin oil with sidr honey and trigona honey has the same hepatoprotective effectiveness. Keywords: Liver, Sidr honey, Trigona honey, Black cumin oil, Paracetamol, SGOT, SGPT